(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Neurotoxins produce molecular and biochemical processes that suggest early-stage effects on exposed people much before or below open illness development. Studying these early occurrences may be a legitimate way to create neurotoxicity indicators in those exposed to chemical substances in the environment. Any use of biochemical markers seems to be more difficult than in other areas in neurotoxicology given the complex nature of the function of both the central neural system, the multilevel character of neurotoxic events and also the lack of access of the objective tissue. Moreover, the evaluation of exposure, subclinical effects and vulnerability to neurotoxic diseases has been established in recent years. This article addresses new biomarkers of neurotoxicity within occupational medicine and its prospects and drawbacks.